PENGARUH DOSIS PROBIOTIK YANG BERBEDA TERHADAP PERTUMBUHAN BENIH IKAN BAWAL (COLOSSOMA MACROPOMUM) - PEBRIAWAN, WIRA; AMINULLAH, AMINULLAH; ASTUTI, NI KADEK PUJI (Ganec Swara, 2025)
Pomfret fish (Colossoma macropomum) is a popular freshwater consumption fish with high demand so it has wide open market prospects. There is a very urgent demand to increase pomfret fish production, especially in fish growth. The aim of this research is to find the optimal dose of probiotics for the growth of pomfret fish (Colossoma macropomum). This research was conducted for 30 days in the Sehati Pokdakan Group. This study used a Completely Randomized Design (CRD) with a total of 4 treatments, namely P0 (0%, as control), P1 (0.005 ml/g feed), P2 (0.010 ml/g feed), P3 (0.015 ml/g feed) with repetition 3 times in each treatment. Based on the research results, the best growth in weight and length was found in P3, namely with a weight value of 12.27 grams and a length of 2.73 cm. The highest specific growth rate was P3 at 1.67%/day and the survival rate reached 96.67%. The lowest (best) average value of feed conversion ratio was found at P3 at 0.53. Meanwhile, air quality during the research was still within the optimal range for pomfret fish, namely temperature 27-29 oC, pH 7.2-8.2, DO 5.3 mg/l, and ammonia 0.1mg/l. The results of the ANOVA test showed that giving different probiotic doses had an effect on the growth of pomfret fish seeds.